Evaluating the difference of skin elasticity value on the use of 3% superoxide dismutase cream and 10% urea - Mawardi, Prasetyadi; Yanuar, Frieda (Journal of Pakistan Association of Dermatologists, 2022)
Introduction: Skin is the outermost layer and the largest organ in the human body which has important role against extrinsic factors such as physical, chemical trauma, and exposure to ultraviolet (UV), which cause damage to its barrier function and induce photoaging, resulting in decreased skin elasticity. Furthermore, urea is a humectant moisturizer that repairs the skin barrier, while superoxide dismutase (SOD) is an antioxidant group commonly used in a series of skin care products. Objective: The study aims to investigate the difference in the value of skin elasticity in the use of 3% SOD and 10% urea cream. Methods: This experimental analytical study was conducted in Dermatotology and Venereology Department outpatient clinic of Dr. Moewardi General Hospital between October-December 2020. Patients with skin disorders and works outdoors were excluded from this study. Superoxide dismutase 3% and urea 10% cream was applied twice daily on the patient’s right and left forearm, respectively for a month. Furthermore, the elasticity values of the skin were assessed in week 2 and 4. All data were statistically analyzed with paired t-test and a p value of < 0.05 was considered significant. Results: The results showed that all the subjects (20) had skin elasticity improvement. However, SOD gave a better skin elasticity (p=0.001) than urea cream (p=0.002). Conclusion: Antioxidant SOD cream has better effect in improving skin elasticity compared to urea.